Implementation of Government Policy in Addressing Junior High School (SMP) Dropouts in Pesisir Selatan Regency - Nici Amanda; Syamsir Syamsir (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Junior high school dropout remains a persistent structural challenge in Pesisir Selatan Regency. During the 2023–2024 academic year, the Department of Education and Culture recorded 1,663 junior high school dropouts, with a dropout rate of 0.07%, exceeding the rates reported in Padang City (0.03%), Solok Regency (0.008%), and Solok City (0.003%). This condition persists despite the implementation of several government initiatives, including the Nine-Year Compulsory Education Program, School Operational Assistance (BOS/BOSDA), the Indonesia Smart Program (PIP), and the 2021–2026 Regional Medium-Term Development Plan (RPJMD). This study aimed to analyze the implementation of government policies, identify implementation constraints, and examine the measures undertaken to address junior high school dropout in Pesisir Selatan Regency. A descriptive qualitative approach was employed. Informants were purposively selected and included officials from the Junior High School Division of the Department of Education and Culture, school principals, guidance and counseling teachers, school dropouts, and parents from SMPN 9 Koto XI Tarusan, SMPN 3 IV Jurai, and SMPN 1 Batang Kapas. Data were collected through semi-structured interviews and documentation, validated through source triangulation, and analyzed using the Miles and Huberman interactive model. The analysis was guided by George C. Edwards III’s policy implementation framework, encompassing communication, resources, disposition, and bureaucratic structure. The findings indicate that the policies have been formally implemented, but their effectiveness is constrained by five interrelated factors: families’ economic burdens, particularly indirect educational costs; inadequate communication regarding access to non-formal education pathways; inconsistent procedures for removing students from the Basic Education Data System (Dapodik); peer-group influence and early marriage; and limited parental involvement, which primarily results from economic constraints rather than parental neglect. In response, the local government, schools, and guidance and counseling teachers have redirected school dropouts to Community Learning Activity Centers (PKBM), strengthened mentoring and home-visit programs, expanded educational assistance, and increased oversight of BOS fund utilization. The study concludes that reducing school dropout in high-risk regions requires the simultaneous strengthening of all four dimensions of Edwards III’s policy implementation framework while ensuring that interventions remain responsive to local socioeconomic and cultural conditions. These findings contribute to educational policy implementation by demonstrating the need for integrated financial, administrative, communicative, and socio-cultural interventions to improve school retention.